Meningkatan Pengetahuan & Minat Berwirausaha Dalam Membentuk Karakter Mandiri Siswa SMAN 10 Pekanbaru - Wiko rusmansyah (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2022)
Entrepreneurship or what is now that most popular as “entrepreneurship” is an activity that is being prioritized by the government for millennials. The government really wishes that millennials who have graduated from school or college should not always think of always looking for work, but rather have an independent character to become entrepreneurs or create their own jobs. In connection with entrepreneurship and fostering an independent character, this time community service wants to see the “entrepreneur” side of public high school students 10 Pekanbaru. This decision was made because we wanted to see the public high schools (outside technical high schools) which usually tend to choose continue their education to a higher level of education than to continue the entrepreneurial stage.